2022
DOI: 10.1007/s00011-022-01611-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine storm: behind the scenes of the collateral circulation after acute myocardial infarction

Abstract: At least 17 million people die from acute myocardial infarction (AMI) every year, ranking it first among causes of death of human beings, and its incidence is gradually increasing. Typical characteristics of AMI include acute onset and poor prognosis. At present, there is no satisfactory treatment, but development of coronary collateral circulation (CCC) can be key to improving prognosis. Recent research indicates that the levels of cytokines, including those related to promoting inflammatory responses and ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…Leukocytes are recruited to the damaged myocardium, but the myocardium away from the infarct is also inflamed, which may be responsible for the remodeling of the non-infarcted myocardium [ 28 ]. At the same time, a large number of cytokines such as TNF-α, IL-6, IL-10, and IL1 are released into the blood, which participate in physiological processes such as inflammatory response and angiogenesis, and affect the remodeling of the heart and the establishment of collateral circulation [ 29 , 30 ]. Toll-like receptor (TLR) signaling pathway and TNF signaling pathway in the KEGG enrichment results also connect AMI and IHF.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytes are recruited to the damaged myocardium, but the myocardium away from the infarct is also inflamed, which may be responsible for the remodeling of the non-infarcted myocardium [ 28 ]. At the same time, a large number of cytokines such as TNF-α, IL-6, IL-10, and IL1 are released into the blood, which participate in physiological processes such as inflammatory response and angiogenesis, and affect the remodeling of the heart and the establishment of collateral circulation [ 29 , 30 ]. Toll-like receptor (TLR) signaling pathway and TNF signaling pathway in the KEGG enrichment results also connect AMI and IHF.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al ( 33 ) found that ICAM1, an adhesion molecule that recruits inflammatory cells from myocardial tissues, was increased in animal models of CMVD and that the expression of pro-inflammatory factors IL-6 and monocyte chemotactic protein 1 (MCP-1) was elevated in cardiac myocytes. Another study found that increased release of inflammatory factors leads to impaired vascular endothelial barrier function after coronary artery occlusion ( 34 , 35 ). Qin et al ( 36 ) found that the expression of inflammation-related factors TNF-α and IL-1β was increased in an in vitro and in vivo model of CMVD.…”
Section: Relationship Between Inflammatory Response and Cmvdmentioning
confidence: 99%
“…Massive researches have demonstrated the role of cytokines in MI that cytokines not only form a complex network to regulate inflammatory response, but also can form cytokine storm to worse myocardium injure following cardiac decompensation ( He et al, 2022 ). Upon cardiac injury, the inflammatory signaling molecules immediately increased.…”
Section: Pathophysiology Of Post-mi Cardiac Fibrosismentioning
confidence: 99%
“…As a family of signal-dependent transcription factors, nuclear factor kappa B (NF-κB) is located in the cytoplasm in an inactive form, but it migrates to the nucleus following stimulation, and regulates its targets via binding to NF-κB response elements on the DNA ( Li and Verma, 2002 ). As a typical pro-inflammatory signaling pathway, NF-κB regulates gene transcription and promotes inflammatory responses ( He et al, 2022 ), for example, exendin-4 regulates the NF-κB axis to prevent inflammation and cardiac remodeling ( Eid et al, 2020 ), and Nur77 improves cardiac fibrosis by inhibiting the NF-κB-dependent pathway ( Chen et al, 2021a ). Further, hippo pathways are vital mechanisms of cardiac repair.…”
Section: Pathophysiology Of Post-mi Cardiac Fibrosismentioning
confidence: 99%